2014
DOI: 10.5327/z2317-4889201400020012
|View full text |Cite
|
Sign up to set email alerts
|

Aptian/Albian (Early Cretaceous) paleogeography of the South Atlantic: a paleontological perspective

Abstract: Paleontological data obtained in recent years reinforce the hypothesis that Aptian marine sedimentation in the sedimentary basins of the Brazilian continental margin -except the Pelotas basin, the southernmost Brazilian basin -took place under the domain of waters coming from the north through the Tethys Sea (Central Atlantic). Tethyan waters could reach the basins of the Brazilian continental margin via the seaway then existing in the present-day region of northeastern Brazil. Here there are records in severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
1
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(86 citation statements)
references
References 34 publications
1
68
1
11
Order By: Relevance
“…Nevertheless, as pointed out by Arai (2014), the Late Aptian to Early Albian marine ingression in the Araripe Basin is long-established (Beurlen 1962, Beurlen 1971a, Beurlen 1971b, Mabesoone & Tinoco 1973, Coimbra et al 2002, as indicated by the presence of echinoids (Beurlen 1966, Manso & Hessel 2012, as well as microfossils, such as dinoflagellates (Arai & Coimbra 1990, Coimbra et al 2002. On the other hand, the Tethyan affinity is undoubtedly assumed by the author based on the occurrence of members of the Subtilisphaera ecozone recorded in the São Luís, Ceará, Parnaíba and Araripe basins.…”
Section: Letter To the Editormentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, as pointed out by Arai (2014), the Late Aptian to Early Albian marine ingression in the Araripe Basin is long-established (Beurlen 1962, Beurlen 1971a, Beurlen 1971b, Mabesoone & Tinoco 1973, Coimbra et al 2002, as indicated by the presence of echinoids (Beurlen 1966, Manso & Hessel 2012, as well as microfossils, such as dinoflagellates (Arai & Coimbra 1990, Coimbra et al 2002. On the other hand, the Tethyan affinity is undoubtedly assumed by the author based on the occurrence of members of the Subtilisphaera ecozone recorded in the São Luís, Ceará, Parnaíba and Araripe basins.…”
Section: Letter To the Editormentioning
confidence: 99%
“…By considering this, we suggest that several data on distinct areas of Geology (i.e., sedimentology, structural geology, stratigraphy and paleontology) should not be overlooked when aiming a more precise paleogeographic scenario. Our purpose in this comment is to take part of this discussion and highlight that a multidisciplinary approach must be addressed in order to confirm or refute the paleogeographic model proposed by Arai (2014). In our opinion, an integrated paleogeographic reconstruction must be based on 1. the number of Tethyan versus austral fossil representatives and their accurate stratigraphic occurrence, 2. the precise timing of the first marine ingression in the continent interior, 3. the basin-filling pattern and stratigraphic architecture of the depositional sequences, 4. paleocurrents and other paleogeographic indicators, and 5. the continental paleotopography and paleodrainage.…”
Section: Letter To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…The basin encompasses alluvial fan deposits (Salvador Formation), lacustrine deposits (Candeias Formation), deltaic deposits (Ilhas Group), and fluvial deposits (São Sebastião Formation) (Magnavita 1992, Magnavita et al 1994, Costa et al 2007a, 2007b, covered by the Marizal Formation, a thin succession of fluvial deposits with a record of marine incursion (e.g. Arai 2014, Amaral & Brito 2012, deposited during a late reactivation of the rift .…”
Section: Geological Settingmentioning
confidence: 99%